Die Auswirkung variabler Meereisrauigkeit auf die atmosphärische Grenzschicht - Ropers, Malte (Universität Bremen, 2013)
The sea ice surface is characterized by a varying degree of roughness with partly abrupt transitions. The roughness is caused by edges of ice floes and brash ice as well as by ridges, hummocks and other structures typical for the sea ice surface. It affects the interaction between the ice and the atmospheric boundary layer. This study deals with the parameterization of the sea ice surface roughness and its influence on the transfer of momentum. Based on data from a number of field campaigns during which different meteorological and ice parameters were measured from aircraft, different approaches for the calculation of the drag coefficient as a function of the sea ice surface structure parameters were compared. For the parameterization of the atmospheric drag coefficient three different approaches were used: (i) relating the drag coefficient to simple geometrical parameters describing the sea ice topography, (ii) partitioning of the total drag into skin and form drag and linking these to ice surface properties, and (iii) high-pass filtering of the surface roughness spectrum and relating the drag coefficient to certain spectral ranges. For the first approach the dependence of the drag coefficients on 10 km averages of the ridge height, distance between ridges, and the aspect ratio was considered. For all parameters statistically significant correlations were found. From the results, it can be concluded that the influence of the aspect ratio on the drag coefficients is more pronounced than the influence of ridge height and distance. The second approach is based on Arya (1975) according to which the total vertical flux of momentum can be expressed as the sum of a skin effect, representing the micro-scale roughness of the surface, and of a form effect which results from the influence of single obstacles such as ridges. Two different concepts of drag partitioning were investigated. Both concepts work fairly well and are slightly superior to the method calculating the surface drag as a function only of the ridge height ...